The Effect of Dietary Lactic Acid Bacteria on Intestinal Microbiota and Immune Responses of Crucian Carp (Carassius auratus) Under Water Temperature Decrease - Liu, Yuan; Lv, Haoxin; Xu, Liping; Zhang, Kun; Mei, Yan; Chen, Jun; Wang, Min; Guan, Yifei; Pang, Huili; Wang, Yanping; Tan, Zhongfang (Frontiers in Microbiology, 2022)
Temperature changes have a great impact on fish feeding, intestinal microorganisms, metabolism and immune function. Therefore, it is necessary to develop effective methods to enhance the survival rates and growth of fish under water temperature changes. Lactic acid bacteria (LAB) is a promising immunostimulatory feed additive, as demonstrated by their beneficial effects in several fish species. This study investigated the short term effects of dietary LAB on intestinal microbiota composition and immune responses of crucian carp (Carassius auratus) when water temperature decreased from 30±1 ℃ to 18 ±1 ℃. Lactococcus (L.) lactis 1209 and L. lactis 1242 with potential probiotics isolated from the intestine of Qinghai naked carp (Gymnocypris przewalskii) were selected as feed additives for the crucian carp feeding experiment. A total of 225 commercially available healthy crucian carp (250 ± 10 g) of similar age were kept in 30 ℃ water for a week and then immediately transferred to 18 ±1 ℃ water, assigned to three dietary treatments for a 16-day feeding trial randomly: (1) HC, diets without additives (the control group); (2) HT, diets with 106 CFU/mL L. lactis 1209, and (3) HL, with 106 CFU/mL L. lactis 1242. Each group was set up with 3 replicates and each with 25 fish. The results showed that the mortality rate of crucian carp in HC, HT and HL group was 50%, 27% and 33%, respectively. High-throughput sequencing results displayed that the composition of the intestinal microorganism varied dynamically in reponse to different treatments and water temperature decrease, among them, compared with the HC group, a higher abundance of Firmicutes and Proteobacteria, and a lower of Actinobacteria appeared in HT and HL. The cytokines heat shock protein 70 (HSP-70) in crucian carp intestinal tract significantly decreased when water temperature decreased (P <0.05).